Growth and characterization of high-density mats of single-walled carbon nanotubes for interconnects - Robertson, J; Zhong, G; Telg, H; Thomsen, C; Warner, J; Briggs, G; Dettlaff-Weglikowska, U; Roth, S (2008)
We grow high-density, aligned single wall carbon nanotube mats for use as interconnects in integrated circuits by remote plasma chemical vapor deposition from a Fe- Al2 O3 thin film catalyst. We carry out extensive Raman characterization of the resulting mats, and find that this catalyst system gives rise to a broad range of nanotube diameters, with no preferential selectivity of semiconducting tubes, but with at least 13 of metallic tubes. © 2008 American Institute of Physics.